DWITUNGGAL DALAM DIMENSI LONTAR: DUALISME DALAM PENCIPTAAN SENI LUKIS - I Made Bendi Yudha (Imaji, 2006)
Art is an expression of feeling representing the crystalization of ideasthat result from imaginative experiences through observation and exploration ofsuch social life as religion, culture, custom and tradition, and naturalenvironment. These are all encouraged by internal stimulus and intuitive urgethat stimulate emotion and imagination to be expressed in a painting art.To Balinese people, lontar is one of the human cultural achievementscontaining dual values and spiritual teaching to guide people to have a physicallyand mentally harmonious and balanced social life. The observed andcomprehended values contained in lontar have inspired the writer during thecreative process.By understanding the balance concept of contained in lontar we canwisely interpret the phenomena of life in our recent social environment which ischaracterized by intrigues of personal interests and violation of moral norms thatresult in horizontal conflicts as represented by the changes of life style andmental attitude such as damaged environment, degraded human value and status,pressure to others, and so on.The understanding of the values has inspired to visualize thephylosophical and conceptual context in the painting artwork of abstractive andrepresentative form with variative colors by impasto technique to have artisticpersonal symbols.Keywords: painting, dual dimension of life